Pengaruh Konsentrasi Sukrosa Terhadap Karakteristik Minuman Probiotik Susu Almon Dengan Isolat Lactobacillus rhamnosus SKG34 - Bayu Setiawan; Komang Ayu Nocianitri; Ni Nyoman Puspawati (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Probiotic drinks contain a number of good bacteria that are beneficial for the body. Plant-based probiotic drinks are an alternative that is not widely known. The aim of this research was to determine the effect of sucrose concentration on the characteristics of probiotic almond milk drinks fermented with Lactobacillus rhamnosus SKG34 and to determine the appropriate sucrose concentration to produce probiotic almond milk with the best characteristics. This research used a Completely Randomized Design (CRD) that consists of 5 levels sucrose concentration 0, 3 6, 9, and 12 percents. Each treatment was repeated 3 times to obtained 15 experimental units. The data were analyzed by Analysis of Variance (ANOVA) and if there was a significant effect (P<0,05), then proceed with the Duncan Multiple Range Test (DMRT) at 5 percents error. The results showed that sucrose concentration had a very significant effect (P<0.01) on sugar total, aroma, taste, sweetness and overall acceptability. Sucrose concentration of 6 percent produced the best probiotic almond milk drinks characteristics with LAB total of 8.76 log cfu/ml, acidity degree of 6.22, acid total of 0.15 percent, sugar total of 6.51 percent, sensory characteristic showed that color was liked, aroma rather was liked, preferred sweet and not sour taste, and overall acceptance was liked.